Development of a physics teaching module integrated with islamic theology on light to improve students' religious values and learning outcomes - Ahmad Labibul Fikri; Faisal Kamal; Fatiatun (Karst: Jurnal Pendidikan Fisika dan Terapannya, 2026)
. The integration of science and Islamic values in physics learning is an effort to develop academic abilities while strengthening students' religious character. This study aims to develop a physics teaching module integrated with Islamic theology on the topic of light and to determine its feasibility, practicality, and effectiveness in learning. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The results show that the developed teaching module is suitable for use in physics learning, declared valid, and capable of supporting improved learning outcomes as well as strengthening students' religious values. Thus, the physics teaching module integrated with Islamic theology on the topic of light can serve as an alternative teaching material that connects physics concepts with Islamic values.